First report of Neofusicoccum ribis causing stem blight and dieback of blueberry (Vaccinium corymbosum) in Michigan - Heger, Lexi; Giraud, Deenarah; Miles, Laura Avila; Byrne, Jan; Miles, Timothy D (Plant disease, 2023)
In July 2020, a 3-year-old 'Envoy' northern highbush blueberry bush (Vaccinium corymbosum L.) from a commercial farm in Van Buren County, Michigan was submitted to the Plant & Pest Diagnostics laboratory at Michigan State University. Field disease assessments across the 2-acre planting were an incidence of 2-5% and a severity of 50-100%. Symptoms included red shoot flagging and dead shoots retaining dry leaves, shoots with light green leaves and necrotic margins, and brown-black cankers at the base of the symptomatic shoots. Shoot sections displaying wood discoloration were surface disinfested by dipping in 95% ethanol and flame sterilized. The internal discolored tissues (0.5 cm2) were plated onto 1% ampicillin and streptomycin, quarter-strength potato dextrose agar (PDA) and incubated at room temperature until fungal colonies were observed. A fungus with rapid growth, developing white and then dark gray mycelium, resembling species in the family Botryosphaeriaceae was isolated and subcultured. After DNA extraction and amplification, sequences of three loci were obtained: the internal transcribed spacer (ITS) region, β-tubulin (Bt), and elongation factor 1-α (EF1) using primer pairs ITS1/ITS4, Bt2a/Bt2b, and EF1-728/EF1-986R, respectively (Slippers et al. 2004). The sequences showed 100% identity with Genbank numbers KF766205 (ITS region, 562 bp - OP588109), MT592721 (Bt, 436 bp - OP585548), and MT592229 (EF1, 306 bp - OP585547) of N. ribis (Slippers et al. 2013, Zhang et al. 2021). Sequences were identified using PopSet 1995604550 (Zhang et al. 2021). Pathogenicity was tested on 2-year-old 'Blueray' blueberries. Five plants, 3 shoots per plant (n = 15) were surface-sterilized with a 3% bleach solution by rinsing, wounded with razor blades using a scratching method in 'X' patterns across the length of the wound, and then inoculated using mycelium plugs (5 mm) from 7-day old cultures grown on full-strength PDA. Plugs were crushed and spread onto the wound and the wound was wrapped with parafilm. Control plant shoots (n = 9) were mock inoculated using sterile PDA plugs. Plants were maintained in the greenhouse at 23°C under a 14-hour photoperiod and imaged at 0-, 7-, and 12-days post inoculation (dpi). Symptoms began developing within 7 dpi. At 12 dpi, 9 of 15 inoculated shoots began displaying leaf necrosis and deep red or brown stem discoloration 6 cm above and below the wound, while controls remained healthy. Fungi morphologically identical to the original isolate were reisolated from sections taken from 2.5, 6.3, and 7 cm above and below the inoculation site. Species identity was confirmed by sequencing as described above. Neofusicoccum species are widespread and commonly associated with canker and dieback symptoms of blueberries (Flor et al. 2022). To our knowledge, this is the first report of stem blight and dieback caused by N. ribis in Michigan blueberry production. The species N. parvum and N. ribis have been reported on southern highbush blueberries in California (Koike et al. 2014) and Florida (Wright and Harmon 2010), but neither has been reported on blueberry in Michigan. Accurate diagnoses of Botryosphaeria fungal species in blueberries is critical for effective disease control and yield loss reduction.